Characterization of Amide Bond Conformers for a Novel Heterocyclic Template of N-acylhydrazone Derivatives - Alexandra Basilio Lopes; Eduardo Miguez; Arthur Eugen Kümmerle; Victor Marcos Rumjanek; Carlos Alberto Manssour Fraga; Eliezer J. Barreiro (Molecules, 2013)
Herein we describe NMR experiments and structural modifications of 4-methyl-2-phenylpyrimidine-N-acylhydrazone compounds (aryl-NAH) in order to discover if duplication of some signals in their 1H- and 13C-NMR spectra was related to a mixture of imine double bond stereoisomers (E/Z) or CO-NH bond conformers (syn and anti-periplanar). NMR data from NOEdiff, 2D-NOESY and 1H-NMR spectra at different temperatures, and also the synthesis of isopropylidene hydrazone revealed the nature of duplicated signals of a 4-methyl-2-phenylpyrimidine-N-acylhydrazone derivative as a mixture of two conformers in solution. Further we investigated the stereoelectronic influence of substituents at the ortho position on the pyrimidine ring with respect to the carbonyl group, as well as the electronic effects of pyrimidine by changing it to phenyl. The conformer equilibrium was attributed to the decoplanarization of the aromatic ring and carbonyl group (generated by an ortho-alkyl group) and/or the electron withdrawing character of the pyrimidine ring. Both effects increased the rotational barrier of the C-N amide bond, as verified by the DG≠ values calculated from dynamic NMR. As far as we know, it is the first description of aryl-NAH compounds presenting two CO-NH bond- related conformations.